Correlation between quantitative liver and spleen volumes and disease severity in primary sclerosing cholangitis as determined by Mayo risk score. Issue 108 (November 2018) - Khoshpouri, Pegah; Ameli, Sanaz; Ghasabeh, Mounes Aliyari; Pandey, Ankur; Zarghampour, Manijeh; Varzaneh, Farnaz Najmi; Jacob, Angela; Pandey, Pallavi; Luo, Yan; Kamel, Ihab R.
Highlights: Liver and spleen volumetries correlate with Mayo risk score in patients with primary sclerosing cholangitis (PSC). The L/T ratio is the best quantifiable volumetric marker to correlate with and predict the disease severity in PSC. Liver volumetry may potentially be useful in supplementing Mayo risk score and predicting disease severity of PSC. Abstract: Objectives: To correlate total and lobar liver and spleen volume with disease severity in primary sclerosing cholangitis (PSC) as determined by Mayo risk score. Methods: This HIPAA-compliant single center retrospective study included 147 PSC patients with available imaging studies (MRCP/CT) and laboratory data between January 2003 and January 2018. Total and lobar (right, left and caudate) liver volume and spleen volume were measured. ANOVA test was performed to assess the differences in volumes between low, intermediate and high-risk groups (Mayo risk score< 0, >0 and< 2, >2, respectively). Correlations between volumes and Mayo risk score were calculated. ROC analysis was performed to assess the accuracy of the variable with the strongest correlation to PSC severity to predict Mayo risk score. P value <0.05 was considered statistically significant. Results: The mean age of this cohort was 45 ± 17 years; 58% were men. Absolute volumes of left lobe, caudate and spleen and volume ratios of left lobe and caudate to total liver volume of the high-risk group were significantly higher compared to those of low and intermediate risk groups (p < 0.05). Left lobe to total liver volume ratio had the highest correlation to Mayo risk score (Pearson correlation coefficient 0.61, p < 0.05) and on ROC analysis it had 84.4% accuracy in detecting high-risk PSC. Conclusions: In this single institution large cohort study, the left lobe to total liver volume ratio was the best quantifiable volumetric biomarker to correlate with severity of PSC as identified by Mayo risk score.